Guideline for Competitive Advantage and Service Innovation for Restaurant Business 4.0 to Encourage and Develop Phuket a Gastronomy Creative City - Chaiyasain, Chainun (Dusit Thani College Journal, 2020)
The restaurant business operation aims to drive competiveness and integrate new service innovation to adjust and promote Phuket as a gastronomy creative city. The synthesized results reveal that restaurant entrepreneurs need to improve working operation so as to adjust with rapid tourism changing situation and a variety of target groups. The food tourist spends their time and budget on the third most popular activities in Phuket. Therefore, to succeed in this concept restaurant entrepreneurs should consider to apply marketing mix concept “8ps” (product, price, place, promotion, people, physical evidence and presentation, process and partnership) and restaurant development that focuses on “PHUKET’s” Products design, Human Resources Development, Uniqueness, Knowledge Management, Environmental Friendly, Technology System, and Stakeholders to support restaurant development to be efficient and sustainable as Phuket’s restaurant business 4.0.